Characterizing end-to-end packet reordering with UDP traffic - Tinta, S.P.; Mohr, A.E.; Wong, J.L. (2009 IEEE Symposium on Computers and Communications, 2009)
Packet reordering (RO) is an Internet event that degrades the performance of both TCP and UDP-based applications. In this paper, we present an end-to-end measurement study of packet reordering of UDP traffic. The goal of our measurement study is to characterize packet reordering in the current Internet as it is reflected by PlanetLab infrastructure. Overall, our analysis shows that current UDP traffic reordering is consistent to prior 1990's studies, despite increased Internet load and technology advancements. In addition, our study adds to the previous results by identifying additional reordering characteristics. More specifically, we show that packet reordering is asymmetric as well as temporal and site-dependent, packet size does influence the likelihood of reordering, that there exists a time-of-the-day dependency, and reordering primarily exists at two timescales (a few milliseconds or multiple tens of milliseconds).